Controlling the luminescence in K2Th(PO4)2:Eu3+ by energy transfer and excitation photon: a multicolor emitting phosphor. (19th August 2020) - Gupta, Santosh K.; Rajeshwari, B.; Achary, S. N.; Tyagi, A. K.; Kadam, R. M.
Abstract : This work highlighted green, red, and white light emission from a single K2 Th(PO4 )2 compound consisting of actinide and an alkali ion through defect, doping, excitation, and energy transfer manipulation. Abstract : This work highlights the role of defects, excitation energy, and energy transfer in realizing color-tunable Green → Red → White from a single phosphor. In this work, thorium-based K2 Th(PO4 )2 :Eu 3+ (KTPE) phosphor was explored for the first time. Rietveld refinement of the powder XRD data showed the formation of a phase pure compound and a reduction in the lattice parameters upon europium doping. Undoped K2 Th(PO4 )2 (KTP) depicted bright green emission under UV irradiation due to the presence of oxygen vacancies (OVs) in the lattice. Further upon host excitation with 250 nm, complete host-to-Eu 3+ energy transfer occurred to produce red emission due to 5 D0 → 7 F2 transition of europium ions with high asymmetry and a branching ratio with an internal quantum yield (IQY) of 53%. On the other hand, under europium excitation with 395 nm, emission spectra displayed host as well as europium emission, producing near white emission with an IQY of 49%. There were slightly more non-radiative channels under dopant excitation compared to the host. Evaluation of the color coordinates and correlated color temperature suggested that the white light was neutral with perfect amalgamation of red, green, and blue. Lifetime spectroscopy suggested a monoexponential decay behavior owing to the stabilization of Eu 3+ at Th 4+ ion, leading to the formation of oxygen vacancies and antisite defects. These defects together with the size and charge mismatch produce substantial lattice strain in the KTPE. Such lattice strain combined with the host crystalline field leads to substantial Stark splitting, in turn to a reduction in the symmetry of KTPE. This work gives a complete flavor of structure–property correlation in designing a new color tunable phosphor by controlling defects, excitation energy, and host-to-dopant energy transfer in the complex phosphate host consisting of alkali and actinide ions.